UNHCR Policy and Its Impact on Refugees in Malaysia: A Critical Assessment in 2025 - Alammari , Mohammed Arafat (مجلة الشرق الأوسط للعلوم الإنسانية والثقافية, 2026)
The goal of this research paper is to critically examine the impact of the United Nations High Commissioner for Refugees (UNHCR) on refugee protection in Malaysia, a country that is a non-signatory to the 1951 Refugee Convention. Despite lacking a domestic asylum framework, Malaysia hosts over 200,000 refugees. This study evaluates how UNHCR policies shape refugee lives, particularly in light of developments up to 2025, including the Tracking Refugees Information System (TRIS) and Malaysia’s suspension of UNHCR access to detention facilities. Grounded in realism, sovereignty, and securitization theory, the paper employs a critical analysis of state-centric migration control versus humanitarian imperatives. Methodologically, the study relies on desk research, synthesizing UNHCR reports, NGO documentation, and regional policy papers. The main argument advanced is that while UNHCR remains essential for survival, its policies are structurally constrained by state sovereignty, leaving refugees in a state of “permanent temporariness”. The findings underscore the need for Malaysia to adopt asylum legislation and for ASEAN to develop regional protection standards.